Clinical effect of vein of Marshall ethanol infusion on mitral isthmus ablation - Ge, Wei-Li; Lu, Yi-Fei; Li, Tao; Wang, Ye; Yin, Jie; Li, Xin-Ran; Jiang, Jian-Jun; Mi, Ya-Fei; Tung, Tao-Hsin; Yan, Su-Hua (Frontiers in Cardiovascular Medicine, 2024)
Purpose This study aimed to investigate the effect of Marshall ethanol infusion (VOM-Et) in the vein on mitral isthmus (MI) ablation. Methods Patients with persistent atrial fibrillation (AF) were grouped into vein of VOM-Et combined with radiofrequency (RF) ablation (VOM-Et-RF) and RF groups. The primary outcome was MI block immediate block rate after surgery. Stratified analysis was also performed for factors affecting the outcome measures. Results A total of 118 consecutive patients underwent AF ablation at Taizhou Hospital of Zhejiang Province from January 2018 to December 2021. Successful bidirectional perimitral block was achieved in 96% of patients in VOM-Et-RF (69 of 72) and in 76% of patients in the RF group (35 of 46) (P < 0.01). In the subgroup analysis, male sex, elder than 60 years, Left atrial diameter <55 mm, and AF duration <3 years were associated with the benefits of VOM-Et in AF Patients. Conclusion The vein of Marshall ethanol infusion for catheter ablation can improve the MI block rate. Male sex, elder age, smaller Left atrial diameter and shorter AF duration may have significant benefits for VOM-Et.